Towards Agriculture 4.0: impact of precision agriculture technology among Malaysia's producers - Mat Su, Ahmad Suhaizi; Tan, Shu Qing (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
There is no doubt that technological advancement eases the routine works of the farmers, alleviate the load, to solve the daily problem faced, as well as for fast decision making. Agriculture 4.0 (Ag4.0) is about boosting the agriculture production by changing the conventional mechanism of producing food, with more advance methods and technique. This includes the used of smart machineries, intelligent robotics equipped with sensors and devices, information technologies and sophisticated decision making tools. The readiness of the technological advancement is highly associated with the economic evaluation and justification, but not limited to a certain type of agricultural production. Precision Agriculture (PA) technologies serve as a tool to manage the farm as well as the crop production activities. The PA serves as a transitional progress between the conventional methods towards Ag4.0 under a new agricultural industry revolution. This will pave a way towards the Agriculture 5.0 on the artificial intelligence (AI) and smart farming production. The megatrends in agriculture sector on Malaysia perspective are, produce differently using a new technique, utilizing the new technology to bring the food to consumers, increasing the efficiency in the food chain and incorporates cross-industry technique and applications.